Efeito magnetoforético aplicado à separação de nanopartículas magnéticas biocompatíveis - SANTOS, Marcus Carrião dos (2011)
In this work a magnetophoretic experiment (MPE) was developed to study the effect of a gradient of magnetic field in the diameter and size dispersivity of nanoparticles in a magnetic fluid (MF). In this experiment, the mass of a permanent magnet is measured by a balance which data varied due to the interaction with the magnetic fluid, which is placed a few centimeters above. Curves of variation of apparent mass of the magnet were obtained as function of time and related to the characteristics of fractions taken from the surface of the MF at different times. The MF consisted of magnetite nanoparticles surface-coated with phosphate. Samples were synthesized by the coprecipitation method and characterization was performed using x-ray diffraction, high resolution transmission electron microscopy (HR-TEM) and vibrating sample magnetometry (VSM). Fractions of the MF were taken during the MPE at five different times. Those fractions were characterized by VSM, from which magnetic diameters were estimated. The magnetic diameters showed a decrease of nanoparticle size in the surface of the MF sample submitted to MPE for longer times of exposure to the field gradient. These same fractions were characterized by HR-TEM and histograms of nanoparticles size distribution were made. Studies of mean and modal (obtained by lognormal fit) diameters had confirmed the behavior indicated by the magnetic diameters showing a decrease of size as function of time. Studies of standard deviation and full width at half maximum (obtained by lognormal fit) had shown a decrease in dispersivity. However, studies of the σ factor were inconclusive, since no significant variations were found for nanoparticles at the experimental size range. Indeed, the MPE results had shown a variation of 16.02% in modal diameter (Dmodal), 14.63% in mean diameter, 30.90% in standard deviation e 33.33% in full width at half maximum between the original sample and the part which was exposed to gradient magnetic field by 60 hours, of fluid with largest initial diameter (Dmodal = 9.24±0.08 nm and σ=0.238±0.009). In addition magnetohyperthemia experiments at 300 kHz were obtained for each sample. Higher specific absorption rates were found for larger particle sizes, which have important applications for cancer treatment. Therefore, we concluded that the magnetophoretic experiment can be used to select the magnetic fluids properties, due to diameter and size standard deviation control, for several technological, environmental and biomedical applications.